Investigating Effective Ways to Maximize the Role of Recruitment Agencies - Dayang Nailul Munna, Abang Abdullah; Ong, Kim Yoke; Ridhawati, Zakaria (Elsevier Ltd., 2013)
The aim of this paper was to investigate the effective ways to maximize the role of recruitment agencies in Malaysia. Kuala Lumpur was chosen as a location of this study. This qualitative study involved 7 informants from 3 categories: the recruitment agency operators, the employers, and the job applicants. In-depth interview was used as a method of data collection. Every response received from the informants was recorded. The findings revealed that the recruitment agencies should focus on recruiting both fresh and post graduates; provide constant training and innovation; increase the agency headcount; conduct industry mapping and carefully search for the clients and candidates; recruit the right candidates; reduce the recruitment fees, screen the good candidates with good working attitudes; stop collecting recruitment fees from candidates, and provide better consultation to ensure its effectiveness. As a conclusion, more research about recruitment agencies should be conducted in order to gain valuable outcome, thus contributing to the human resource field.